2013
DOI: 10.1371/journal.pone.0072385
|View full text |Cite
|
Sign up to set email alerts
|

Odors and Sensations of Humidity and Dryness in Relation to Sick Building Syndrome and Home Environment in Chongqing, China

Abstract: The prevalence of perceptions of odors and sensations of air humidity and sick building syndrome symptoms in domestic environments were studied using responses to a questionnaire on the home environment. Parents of 4530 1–8 year old children from randomly selected kindergartens in Chongqing, China participated. Stuffy odor, unpleasant odor, pungent odor, mold odor, tobacco smoke odor, humid air and dry air in the last three month (weekly or sometimes) was reported by 31.4%, 26.5%, 16.1%, 10.6%, 33.0%, 32.1% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 55 publications
8
56
2
2
Order By: Relevance
“…Previous studies have found that perceived air pollution in indoor environments is influenced by human body odors, building materials, ventilation systems, indoor smoking, and other human activities (Fanger et al, 1988). One study found that cleaning, an activity closely associated with pleasant odors, was a significant factor in reduced symptoms of Sick Building Syndrome (SBS) compared to no-odor conditions (Wang et al, 2013).…”
Section: Olfactory Modulation Behavioral Links Between Odor Mood Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that perceived air pollution in indoor environments is influenced by human body odors, building materials, ventilation systems, indoor smoking, and other human activities (Fanger et al, 1988). One study found that cleaning, an activity closely associated with pleasant odors, was a significant factor in reduced symptoms of Sick Building Syndrome (SBS) compared to no-odor conditions (Wang et al, 2013).…”
Section: Olfactory Modulation Behavioral Links Between Odor Mood Anmentioning
confidence: 99%
“…The effect of odors on moods are critically dependent on past associations and personal preferences for those odors (Herz, 2009). It is important to note that the effects on putative mood states of odor are occasionally assessed relative to a no-odor control, rather than as a comparison between odors (Lehrner et al, 2000;Wang et al, 2013), thus interpreting the efficacy of a given odor relative to others, which could provide insight into neural mechanisms, remains unclear.…”
Section: Olfactory Modulation Behavioral Links Between Odor Mood Anmentioning
confidence: 99%
“…Additionally, humidity exposure can cause muscle cramps, fainting, heat stroke, and even exacerbate the underlying medical conditions, such as lung or heart disease (Zheng et al 2012). Wang et al (2013) investigated the prevalent perceptions of odours and sensations of air humidity and SBS symptoms in domestic environments through questionnaire distributed among 4530 parents of kindergarten children in China. The findings confirmed the significance of humid air's role in symptomizing general signs as well as mucosal and skin sicknesses in children.…”
Section: Sbs Contributors Symptoms and Effectsmentioning
confidence: 99%
“…Pungent odor, musty odor and stuffy odor in multi-family buildings in Sweden were associated with asthma symptoms among adults [65]. Self-report of odor perceptions in dwellings were also found to be associated with SBS among adults in China [87]. Thus, odor perception can be associated with different types of exposure and can be of importance for asthma.…”
Section: Symptoms Factors Subcategorymentioning
confidence: 99%